The Reversible World of Japanese Coalmining Women - Sone, Sachiko (The Australian journal of anthropology, 2007)
This paper illuminates the social world of Japanese coalminers, with special attention given to women miners as told through their oral accounts and work songs, which historians have not used before. These coalmining women constituted the second largest single occupational category in the early part of the 20th century, yet they still continue to receive little scholarly attention. This investigation has led to a new concept of the world of women coalminers, the so-called ‘reversible world’, which operated in a specific social and economic context—the dark underground world of the mine and the light world above of conventional society. Uncovering this underground world has enormous significance in fleshing out the identity and spirit of the miners. It challenges historians' stereotypes of the miners as apolitical, apathetic and unaware of the inequities in their work situation. Mining women created their own world under the ground where normal gender roles were partially reversed.